+0  
 
0
33
1
avatar

how do i work this out

 Jan 31, 2019
 #1
avatar+95866 
+1

Expand   (x + 2) (x - 3) ( x + 5) =

 

( x^2  - x - 6) ( x + 5)  =

 

x^3 - x^2  -  6x + 5x^2 - 5x - 30 =

 

x^3 + 4x^2 - 11x - 30

 

So

 

a = 4      and     b = -30

 

 

 

cool cool cool

 Jan 31, 2019

14 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.